2014
DOI: 10.3171/2014.1.spine13837
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of anterior cervical discectomy and fusion supplemented with transarticular facet screws

Abstract: Object The clinical success rates of anterior cervical discectomy and fusion (ACDF) procedures are substantially reduced as more cervical levels are included in the fusion procedure. One method that has been proposed as an adjunctive technique for multilevel ACDF is the placement of screws across the facet joints (“transfacet screws”). However, the biomechanical stability imparted by transfacet screw placement (either unilaterally or bilaterally) has not been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Previous studies report favorable clinical and radiographic outcomes in patients with single-level cervical radiculopathy secondary to spondylosis treated with posterior cervical spacers or cages placed between the facet joints 5,11. The current study demonstrated that both lateral mass constructs and bilateral posterior cervical cages offer comparable postoperative segmental stability; both techniques significantly decreased cervical ROM in FE, LB, and AR.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies report favorable clinical and radiographic outcomes in patients with single-level cervical radiculopathy secondary to spondylosis treated with posterior cervical spacers or cages placed between the facet joints 5,11. The current study demonstrated that both lateral mass constructs and bilateral posterior cervical cages offer comparable postoperative segmental stability; both techniques significantly decreased cervical ROM in FE, LB, and AR.…”
Section: Discussionsupporting
confidence: 60%
“…30,31 The placement of facet screws have shown biomechanical and clinical promise, but placement above C5 may be limited due to occipital prominence. 10 Corollary issues may arise with placement of interfacet spacers at the lower cervical segments due to inadequate imaging and prominence of the shoulders. Further investigation is needed to determine the feasibility of minimal access placement at all cervical levels.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling segmental motion of the facet joints by blocking with bone graft or interfacet allograft spacers may stabilize the spine and result in spine fusion and indirect foraminal decompression. 10,[12][13][14][15][16][17] Machined interfacet allograft spacers are placed directly into the facet joint and they have a relatively large surface area that stiffens the spinal segment, and potentially increases foraminal height and area to indirectly decompress the neuroforamina. 11,17,18 Interfacet allograft spacers are machined cortical allografts sized 2 to 4 mm in height and contain ridges that provide stability to resist retropulsion.…”
Section: Introductionmentioning
confidence: 99%
“…4,[10][11][12][13][14][15] Mechanistically, the pure moment is applied to the end vertebrae ensuring equal loading to all segments of the spinal column, 1 even as the spine deforms during testing. This has been accomplished in multiple forms with varying complexity and ease of use, including cable and pulley systems, 2,11,13 in which load application is assisted with static weights or load frame actuation, motor-actuated robotic arms, [15][16][17] and hydraulicallyor pneumatically-actuated gimbal systems 10,12,18 that can be configured to apply pure moments at one or both ends of the spinal segment. Stepwise moment application using cable and pulley systems has been the predominant method of flexibility testing 19,20 and is still prevalent in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise moment application using cable and pulley systems has been the predominant method of flexibility testing 19,20 and is still prevalent in the current literature. 14,[21][22][23] More recently, continuous loading of cadaveric spine specimens has been introduced, 10,12,15,18 representing a more physiologic laboratory technique with which to evaluate spine flexibility, with the major advantage that it permits the analysis of the spine's behavior in the neutral zone. 24 Despite the perceived notion that the kinematic response of the test constructs under pure moments applied with the varying approaches are similar, few studies have quantified the differences, if they exist, in intervertebral range of motion (ROM) resulting from laboratory-specific loading apparatuses.…”
Section: Introductionmentioning
confidence: 99%